Method for producing carbon nanotubes

JP7631664B2Active Publication Date: 2025-02-19ZEON CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2019196722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-10-29
Publication Date
2025-02-19
Estimated Expiration
2039-10-29

AI Technical Summary

Benefits of technology

【0015】 本発明のカーボンナノチューブの製造方法によれば、高品質なカーボンナノチューブを効率的に製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631664000001
    Figure 0007631664000001
  • Figure 0007631664000002
    Figure 0007631664000002
  • Figure 0007631664000003
    Figure 0007631664000003
Patent Text Reader

Abstract

To provide a method of producing a carbon nanotube, capable of efficiently producing a carbon nanotube of high quality.SOLUTION: The method of producing a carbon nanotube using a carbon nanotube generating substrate comprising a substrate and a catalyst layer disposed on the substrate, comprises: a first forming process (A) of forming a carbon nanotube on the catalyst layer; a peeling process (B) of peeling off the carbon nanotube formed on the catalyst layer; and a second forming process (C) of forming a carbon nanotube again on the catalyst layer from which the carbon nanotube has been peeled off. In the peeling process (B), the carbon atom concentration on a surface of the catalyst layer from which the carbon nanotube has been peeled off is lower than 50 atom%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing carbon nanotubes, and more particularly to a method for efficiently producing high-quality carbon nanotubes. [Background technology]

[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs") have various excellent properties, such as mechanical strength, optical properties, electrical properties, thermal properties, and molecular adsorption capacity, and are expected to be used as functional materials for electronic devices, optical elements, conductive materials, etc.

[0003] Here, chemical vapor deposition (hereinafter sometimes referred to as "CVD") is known as one method for producing CNTs. This CVD method is characterized by synthesizing CNTs by bringing a carbon compound, which serves as a raw material, into contact with a catalyst consisting of metal fine particles in a high-temperature atmosphere. CVD has attracted attention as a production method that offers a high degree of freedom in CNT production conditions (e.g., type or arrangement of catalyst, type of carbon compound, or reaction conditions), and is capable of producing both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs).

[0004] Among the methods for producing CNTs using the CVD method, the method of synthesizing CNTs using a substrate carrying a catalyst layer made of a CNT synthesis catalyst (hereinafter sometimes referred to as a "CNT production substrate") has attracted particular attention because it allows for the mass production of many CNTs aligned perpendicularly to the CNT production substrate. Therefore, various proposals have been made regarding the method of producing CNTs by the CVD method using a CNT production substrate, with the aim of reducing production costs, etc.

[0005] Specifically, for example, Patent Documents 1 and 2 propose a technology for reducing the cost of CNT production by recovering CNTs formed on a CNT production substrate and then reusing the used CNT production substrate for synthesizing CNTs. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2006-27948 [Patent Document 2] Japanese Patent Application Laid-Open No. 2007-91485 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the above-described conventional CNT manufacturing method, which produces CNTs while repeatedly reusing used CNT-producing substrates, has room for improvement in terms of efficiently producing high-quality CNTs.

[0008] Therefore, an object of the present invention is to provide a method for producing carbon nanotubes that enables efficient production of high-quality carbon nanotubes. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to achieve the above object, and have newly discovered that, when producing CNTs through a first forming step (A) of forming carbon nanotubes on a catalyst layer of a carbon nanotube producing substrate, a peeling step (B) of peeling off the carbon nanotubes formed on the catalyst layer, and a second forming step (C) of forming carbon nanotubes again on the catalyst layer from which the carbon nanotubes have been peeled, if the carbon atom concentration on the surface of the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B) is less than a predetermined value, high-quality carbon nanotubes can be produced efficiently, and have completed the present invention.

[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the carbon nanotube manufacturing method of the present invention is a carbon nanotube manufacturing method that uses a carbon nanotube producing substrate comprising a substrate and a catalyst layer provided on the substrate, and includes a first forming step (A) of forming carbon nanotubes on the catalyst layer, a peeling step (B) of peeling off the carbon nanotubes formed on the catalyst layer, and a second forming step (C) of forming carbon nanotubes again on the catalyst layer from which the carbon nanotubes have been peeled, characterized in that the carbon atom concentration on the surface of the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B) is less than 50 atomic %. If the carbon atom concentration on the surface of the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B) is less than 50 atomic %, high-quality carbon nanotubes can be efficiently produced. In the present invention, the term "carbon nanotube generation substrate" means either a "pre-used CNT generation substrate that has never undergone CNT formation" or a "used CNT generation substrate after CNT formation has been performed on a pre-used CNT generation substrate (including a used CNT generation substrate after further CNT formation has been performed on a used CNT generation substrate)." In the present invention, the "carbon atom concentration" can be measured by the method described in the examples below.

[0011] In the carbon nanotube manufacturing method of the present invention, it is preferable that the carbon nanotubes are formed using a mixed gas containing a carbon nanotube raw material gas and hydrogen in at least one of the first forming step (A) and the second forming step (C). When the carbon nanotubes are formed using a mixed gas containing a carbon nanotube raw material gas and hydrogen in the first forming step (A) and / or the second forming step (C), high-quality carbon nanotubes can be manufactured more efficiently.

[0012] Furthermore, the method for producing carbon nanotubes of the present invention preferably further comprises a washing step (D) of washing the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B). By washing the catalyst layer from which the carbon nanotubes have been peeled, higher quality carbon nanotubes can be efficiently produced.

[0013] Furthermore, the method for producing carbon nanotubes of the present invention preferably further comprises an oxidation treatment step (E) of oxidizing the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B). By subjecting the catalyst layer from which the carbon nanotubes have been peeled to an oxidation treatment, higher quality carbon nanotubes can be efficiently produced.

[0014] Furthermore, the method for producing carbon nanotubes of the present invention preferably further comprises a polishing step of polishing the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B). Such a polishing step is preferably carried out after the cleaning step (D). By polishing the catalyst layer from which the carbon nanotubes have been peeled, higher quality carbon nanotubes can be efficiently produced. [Effects of the Invention]

[0015] According to the method for producing carbon nanotubes of the present invention, high-quality carbon nanotubes can be produced efficiently. DETAILED DESCRIPTION OF THE INVENTION

[0016] Hereinafter, embodiments of the present invention will be described in detail. In the carbon nanotube manufacturing method of the present invention, carbon nanotubes (CNTs) are synthesized on the catalyst layer of a carbon nanotube production substrate comprising a substrate and a catalyst layer provided on the substrate, and the synthesized CNTs are obtained by peeling off the catalyst layer. In the CNT manufacturing method of the present invention, used CNT production substrates (hereinafter sometimes referred to as "used substrates") are reused from the viewpoint of producing CNTs at low cost.

[0017] Specifically, the method for manufacturing carbon nanotubes of the present invention is a method for manufacturing CNTs using a CNT production substrate having a catalyst layer formed thereon, and includes a first formation step (A) of forming CNTs on the catalyst layer, a peeling step (B) of peeling the CNTs formed on the catalyst layer, and a second formation step (C) of reforming CNTs on the catalyst layer from which the CNTs have been peeled. If desired, in the peeling step (B), a cleaning step (D) of cleaning the catalyst layer from which the CNTs have been peeled and / or an oxidation treatment step (E) of subjecting the catalyst layer from which the CNTs have been peeled to an oxidation treatment are further included. In the method for manufacturing CNTs of the present invention, by repeatedly performing the formation and peeling of CNTs, CNTs can be efficiently manufactured while reusing the used substrate.

[0018] <CNT production substrate> The "CNT production substrate" in the present invention may be either the "pre-use CNT production substrate" or the "used CNT production substrate" as described above. The pre-use CNT production substrate can be obtained by forming a catalyst layer on a substrate (sometimes referred to as a "virgin substrate") before being used for CNT synthesis. Note that an underlayer such as a carburization prevention layer or a catalyst support layer may be provided between the substrate and the catalyst layer. In other words, the catalyst layer may be formed on the substrate via an arbitrary layer, that is, it may be formed on the surface of the substrate or on the surface of an arbitrary layer such as an underlayer.

[0019] [Substrate] Here, as the substrate, any substrate can be used as long as it is possible to support a catalyst for CNT synthesis on its surface. Specifically, as the substrate, those having a proven track record in CNT production can be appropriately used. The substrate preferably can maintain its shape even at a high temperature of 400°C or higher.

[0020] Examples of materials for the substrate include metals such as iron, nickel, chromium, molybdenum, tungsten, titanium, aluminum, manganese, cobalt, copper, silver, gold, platinum, niobium, tantalum, lead, zinc, gallium, indium, germanium, and antimony, as well as alloys and oxides containing these metals, non-metals such as silicon, quartz, glass, mica, graphite, and diamond, and ceramics. Among these, metals are preferred because they are less expensive and easier to process than silicon and ceramics, and Fe-Cr (iron-chromium) alloys, Fe-Ni (iron-nickel) alloys, and Fe-Cr-Ni (iron-chromium-nickel) alloys are particularly suitable.

[0021] The shape of the substrate can be a flat plate, thin film, block, or particle, and from the perspective of mass production of CNTs, flat plate and particle shapes are particularly advantageous as they provide a large surface area relative to the volume.

[0022] Here, when a flat substrate is used, there is no particular limitation on the thickness of the substrate, and for example, a thin film of about several micrometers to a thickness of about several centimeters can be used. Preferably, the thickness of the substrate is 0.05 mm or more and 3 mm or less. If the thickness of the substrate is 3 mm or less, the substrate can be sufficiently heated during CNT synthesis, preventing poor CNT growth. In addition, the cost of the substrate can be reduced. On the other hand, if the thickness of the substrate is 0.05 mm or more, deformation of the substrate due to carburization during CNT synthesis can be prevented, and bending of the substrate itself is less likely to occur, which is advantageous for transporting and reusing the substrate. Note that, as used herein, "carburization" refers to the penetration of carbon components into the substrate.

[0023] The shape and size of the flat substrate are not particularly limited, but rectangular or square shapes can be used. The length of one side of the substrate is not particularly limited, but from the viewpoint of mass production of CNTs, a longer side is more desirable.

[0024] [Carburization prevention layer] Here, particularly when a flat substrate is used, the substrate may have a carburization prevention layer as an underlayer on at least one of the front and back surfaces, and the substrate preferably has a carburization prevention layer on both the front and back surfaces. The carburization prevention layer is a protective layer that prevents the substrate from being carburized and deformed during CNT synthesis.

[0025] The carburization prevention layer is preferably made of a metal or ceramic material, and is particularly preferably made of a ceramic material that has a high carburization prevention effect. Examples of metals include copper and aluminum. Examples of ceramic materials include oxides such as aluminum oxide, silicon oxide, zirconium oxide, magnesium oxide, titanium oxide, silica alumina, chromium oxide, boron oxide, calcium oxide, and zinc oxide, and nitrides such as aluminum nitride and silicon nitride. Among these, aluminum oxide and silicon oxide are preferred as materials for the carburization prevention layer because of their high carburization prevention effect.

[0026] The thickness of the carburization prevention layer is preferably 0.01 μm or more and 1.0 μm or less. If the thickness of the carburization prevention layer is 0.01 μm or more, sufficient carburization prevention effect can be obtained. On the other hand, if the thickness of the carburization prevention layer is 1.0 μm or less, changes in the thermal conductivity of the substrate can be suppressed, and the substrate can be sufficiently heated during CNT synthesis to allow good CNT growth. Methods for forming (coating) the carburization prevention layer can include, for example, physical methods such as vapor deposition and sputtering, CVD, and coating methods.

[0027] [Catalyst support layer] The catalyst support layer is a base layer other than the carburization prevention layer, and serves as a base layer for the CNT synthesis catalyst. Various materials can be used as the material for the catalyst support layer as long as they serve as a base layer for the CNT synthesis catalyst. For example, ceramic materials such as alumina, titania, titanium nitride, and silicon oxide are preferably used. Among these, it is preferable to use a ceramic material as the material for the catalyst support layer. This is because ceramic materials allow for better CNT growth when CNTs are synthesized using a reused substrate.

[0028] The thickness of the catalyst support layer is preferably 10 nm or more from the viewpoint of stable CNT growth and improved yield, and is preferably 30 nm or less from the viewpoint of production efficiency.

[0029] [Catalyst layer] The catalyst layer provided on the substrate is a layer containing a CNT synthesis catalyst, such as a metal. The CNT synthesis catalyst preferably contains fine particles of the CNT synthesis catalyst, which are obtained by performing a reduction treatment (formation process described later) using hydrogen or the like before CNT synthesis. The catalyst layer can be formed, for example, by applying a CNT synthesis catalyst solution. Here, the CNT synthesis catalyst constituting the catalyst layer can be, for example, any catalyst that has been used in the past for CNT production. Specifically, examples of CNT synthesis catalysts include iron, nickel, cobalt, and molybdenum, as well as chlorides and alloys thereof. The amount of CNT synthesis catalyst used to form the catalyst layer can be, for example, an amount that has been used in the past for CNT production.

[0030] In addition, either a wet process or a dry process can be used to form the catalyst layer on the substrate. Specifically, methods such as sputtering deposition and coating and baking of a liquid in which metal particles are dispersed in an appropriate solvent can be applied. Furthermore, the catalyst layer can be formed into any shape by combining this with patterning using well-known techniques such as photolithography or nanoimprinting. By adjusting the shape of the catalyst layer formed on the substrate and the CNT growth time, aligned CNT aggregates can be obtained in a variety of shapes, including thin films, cylinders, and prisms.

[0031] When a flat substrate is used, the catalyst layer may be formed on both the front and back sides of the substrate, or on only one side. Forming a catalyst layer on both the front and back sides of the substrate allows CNTs to grow on both the front and back sides of the substrate, improving production efficiency. Of course, depending on production costs, production process convenience, and the like, it is possible to provide a catalyst layer on only one side of the substrate.

[0032] The thickness of the catalyst layer is preferably 0.1 nm or more and 100 nm or less, more preferably 0.5 nm or more and 10 nm or less, and particularly preferably 0.8 nm or more and 3.0 nm or less.

[0033] <First Forming Step (A)> In the first formation step (A), carbon nanotubes are formed on a catalyst layer. Here, in the first formation step (A), CNTs may be formed on a catalyst layer of a pre-used CNT generation substrate that has not been subjected to CNT formation even once, or CNTs may be formed on a catalyst layer of a used CNT generation substrate that has been subjected to at least one CNT formation. When a used CNT generation substrate (used substrate) is reused to produce CNTs, a new catalyst layer may be formed on the catalyst layer (used catalyst layer) of the used substrate in the catalyst layer formation step described below, or the catalyst layer (used catalyst layer) of the used substrate may be used as the catalyst layer without forming a new catalyst layer. Although there are no particular limitations on the method for forming CNTs on the catalyst layer, a preferred method is to heat at least one of the CNT production substrate and the mixed gas containing the CNT source gas and hydrogen in an environment surrounding the CNT production substrate, and grow CNTs by chemical vapor deposition (CVD). This method allows CNTs to be grown on the CNT production substrate with high efficiency, and easily forms an aligned CNT aggregate in which many CNTs grown from the catalyst are aligned in a specific direction. Furthermore, as described above, by forming CNTs using a mixed gas containing hydrogen in addition to the CNT raw material gas, the carbon atom concentration on the surface of the catalyst layer after peeling off the formed CNTs can be reduced.

[0034] More specifically, the formation of CNTs on the catalyst layer in the first formation step (A) is not particularly limited, and can be carried out by sequentially carrying out a formation step in which the catalyst for CNT synthesis in the catalyst layer is reduced, a growth step in which CNTs are grown on the catalyst layer, and a cooling step in which the substrate on which the CNTs have been grown is cooled.

[0035] [Formation process] In the formation process, the environment surrounding the CNT production substrate on which CNTs are formed is changed to an environment containing a reducing gas, and then at least one of the CNT production substrate and the reducing gas is heated to reduce and atomize the CNT synthesis catalyst in the catalyst layer. This formation process produces at least one of the following effects: reduction of the CNT synthesis catalyst, promotion of atomization of the CNT synthesis catalyst, and improvement of the activity of the CNT synthesis catalyst. The temperature of the CNT production substrate and / or the reducing gas in the formation process is preferably 400°C or higher and 1100°C or lower. The formation process is preferably performed for 3 minutes or higher and 30 minutes or lower, and more preferably 3 minutes or higher and 8 minutes or lower. If the formation process is performed for a time within this range, coarsening of catalyst particles is prevented, and the generation of multi-walled CNTs can be suppressed.

[0036] The reducing gas may be, for example, hydrogen gas, ammonia gas, water vapor, or a mixture thereof. The reducing gas may also be a mixed gas obtained by mixing these gases with an inert gas such as helium gas, argon gas, or nitrogen gas. The reducing gas is generally used in the formation step, but may also be used in the growth step as appropriate.

[0037] [Growth process] In the growth process, the surrounding environment of the CNT production substrate is changed to an environment in which a mixed gas containing CNT raw material gas and hydrogen is present, and then at least one of the CNT production substrate and the mixed gas is heated, and CNTs are grown on the reduced and microparticulated catalyst by chemical vapor deposition.

[0038] The CNT source gas in the mixed gas is a gas containing a CNT source material, such as a gas containing a source carbon source at a temperature for CNT growth. Among these, hydrocarbon gases such as methane, ethane, ethylene, propane, butane, pentane, hexane, heptane, propylene, and acetylene are preferred. Other suitable gases include lower alcohol gases such as methanol and ethanol. Mixtures of these gases can also be used.

[0039] The mixing ratio of hydrogen in the mixed gas (volume flow rate of hydrogen / volume flow rate of the entire mixed gas) is preferably 1% by volume or more and 30% by volume or less, and particularly preferably 5% by volume or more and 15% by volume or less. If the hydrogen mixing ratio in the mixed gas is within the above range, the carbon atom concentration on the surface of the catalyst layer after peeling off the formed CNTs can be reduced, and high-quality carbon nanotubes can be efficiently produced.

[0040] The mixed gas may be diluted with an inert gas. The inert gas is a gas that is inert at the temperature at which CNTs grow, does not reduce the activity of the catalyst, and does not react with the growing CNTs. Examples of the inert gas include nitrogen gas; rare gases such as helium gas, argon gas, neon gas, and krypton gas; and mixed gases thereof. Nitrogen gas, helium gas, argon gas, and mixed gases thereof are particularly preferred.

[0041] Furthermore, it is more preferable that the environment surrounding the carbon nanotube growth substrate during the growth process further contains a catalyst activator that enhances catalyst activity and extends the catalyst's active life (catalytic activation effect). The addition of a catalyst activator can further improve the production efficiency and purity of CNTs. Preferred catalyst activators include, for example, oxygen-containing substances that do not significantly damage CNTs at CNT growth temperatures. Specifically, effective catalyst activators include, for example, water, oxygen, ozone, acidic gases, nitrogen oxide, carbon monoxide, carbon dioxide, and other low-carbon oxygen-containing compounds; alcohols such as ethanol and methanol; ethers such as tetrahydrofuran; ketones such as acetone; aldehydes; esters; and mixtures thereof. Among these, water, oxygen, carbon dioxide, carbon monoxide, and ethers are preferred, with water and carbon dioxide being particularly preferred.

[0042] In addition, substances containing both carbon and oxygen, such as carbon monoxide and alcohols, may function as both a feed gas and a catalyst activator. For example, carbon monoxide acts as a catalyst activator when combined with a more reactive feed gas, such as ethylene, and acts as a feed gas when combined with a catalyst activator that exhibits significant catalyst activation even in trace amounts, such as water.

[0043] The temperature to which at least one of the CNT production substrate and the mixed gas is heated may be any temperature that allows CNT growth, but is preferably 400° C. or higher and 1100° C. or lower. A temperature of 400° C. or higher allows the effect of the catalyst activation material to be exhibited well, while a temperature of 1100° C. or lower prevents the catalyst activation material from reacting with the CNTs.

[0044] [Cooling process] In the cooling step, the CNT-grown substrate is cooled in an inert gas environment to prevent oxidation of the CNTs and substrate, which are in a high-temperature state after the growth step, in an oxygen-containing environment. The inert gas used here may be the same as the inert gas that can be used in the growth step. In the cooling step, the temperature of the CNT-grown substrate is preferably lowered to 400°C or lower, more preferably 200°C or lower.

[0045] [Characteristics of CNT] In the first formation step (A) or the second formation step (C) described below, CNTs are usually formed as aligned CNT aggregates on the catalyst layer of the CNT production substrate, and it is preferable that they have, for example, the following properties: That is, the preferred BET specific surface area of ​​the aligned CNT aggregate is 800 m when the CNTs are mainly unopened. 2 / g or more, more preferably 1000m 2 / g or more. The higher the BET specific surface area, the more easily the amount of impurities such as metals and carbon can be reduced to less than several tens of percent (approximately 40%) of the mass of the CNT. Furthermore, CNTs with a large BET specific surface area are effective as catalyst supports and energy / material storage materials, and are suitable for applications such as supercapacitors and actuators. The upper limit of the BET specific surface area is usually set at 2500 m 2 / g.

[0046] The weight density of the aligned CNT aggregates is 0.002 g / cm 3 More than 0.2g / cm 3 It is preferable that the weight density is 0.2 g / cm or less. 3 If the weight density is less than 0.002 g / cm, the bonds between the CNTs constituting the aligned CNT aggregate will be weak, making it easier to disperse the aligned CNT aggregate homogeneously when stirred in a solvent or the like. 3If the above is the case, the integrity of the aligned CNT aggregate can be improved and it can be prevented from falling apart, making it easier to handle.

[0047] Furthermore, it is preferable that the aligned CNT aggregate aligned in a specific direction has a high degree of orientation. Here, having a high degree of orientation means that at least one of the following 1. to 3. is satisfied. 1. When X-rays are incident on a CNT from a first direction parallel to its longitudinal direction and a second direction perpendicular to the first direction and the X-ray diffraction intensity is measured (θ-2θ method), there exist θ angles and reflection directions where the reflection intensity from the second direction is greater than the reflection intensity from the first direction, and there exist θ angles and reflection directions where the reflection intensity from the first direction is greater than the reflection intensity from the second direction. 2. When X-ray diffraction intensity is measured (Laue method) on a two-dimensional diffraction pattern image obtained by irradiating X-rays perpendicular to the longitudinal direction of CNTs, a diffraction peak pattern indicating the presence of anisotropy appears. 3. The Hellman's orientation coefficient is greater than 0 and less than 1, preferably greater than 0.25 and less than 1, when X-ray diffraction intensity is obtained by the θ-2θ method or the Laue method.

[0048] Furthermore, in the X-ray diffraction of the oriented CNT aggregate, it is also preferable that the diffraction intensity of the (CP) diffraction peak and (002) peak due to the packing between the single-walled CNTs differs from the diffraction peak intensity of the (100) and (110) peaks due to the six-membered carbon ring structure constituting the single-walled CNTs in the parallel (first direction) and perpendicular (second direction) incident directions.

[0049] Furthermore, in order for the aligned CNT aggregate to exhibit high orientation and a high BET specific surface area, the height (length) of the aligned CNT aggregate is preferably in the range of 10 μm to 10 cm. A height of 10 μm or more improves orientation. Furthermore, a height of 10 cm or less allows for rapid production, suppressing the adhesion of carbonaceous impurities and improving the BET specific surface area.

[0050] The G / D ratio of the CNT is preferably 1.5 or more, more preferably 2 or more, and even more preferably 2.5 or more. The G / D ratio of the CNT can be 100 or less, and can also be 10 or less. The G / D ratio is an index generally used to evaluate the quality of CNT. The Raman spectrum of CNT measured by a Raman spectrometer contains the G band (1600 cm -1 around 1350 cm -1 A vibration mode called the G band (near the G band) is observed. The G band is a vibration mode originating from the hexagonal lattice structure of graphite, which is the cylindrical surface of the CNT, and the D band is a vibration mode originating from the amorphous part. Therefore, the higher the peak intensity ratio of the G band to the D band (G / D ratio), the more highly crystalline the CNT can be evaluated.

[0051] In this CNT manufacturing method, the CNTs formed on the CNT generating substrate in the first formation step (A) are peeled off in the next peeling step (B), and the substrate is reused.

[0052] <Peeling process (B)> In the peeling step (B), the CNTs formed on the catalyst layer are peeled and recovered from the CNT production substrate. Examples of methods for peeling the formed CNTs from the CNT production substrate include physical, chemical, and mechanical peeling methods. Specifically, methods that can be applied include peeling from the catalyst layer using an electric field, magnetic field, centrifugal force, surface tension, etc.; mechanically peeling directly from the catalyst layer; and peeling from the catalyst layer using pressure or heat. Alternatively, the CNTs can be sucked and peeled off from the catalyst layer using a vacuum pump. Simple peeling methods that are less likely to damage the CNTs include directly picking the CNTs with tweezers to peel them off from the catalyst layer, and peeling the CNTs off from the catalyst layer using a thin blade such as a plastic spatula or cutter blade with a sharp edge. Among these, the preferred peeling method is peeling the CNTs off from the catalyst layer using a thin blade such as a plastic spatula or cutter blade with a sharp edge.

[0053] The peeling step (B) may further include a cleaning step (D) of cleaning the catalyst layer from which the CNTs have been peeled and / or an oxidation treatment step (E) of oxidizing the catalyst layer from which the CNTs have been peeled. The CNT production method of the present invention requires that the carbon atom concentration on the surface of the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B) be less than 50 atomic %. This carbon atom concentration can be determined by measuring the surface of the catalyst layer immediately after the CNTs have been peeled if the cleaning step (D) and / or the oxidation treatment step (E) are not performed. Alternatively, if the cleaning step (D) and / or the oxidation treatment step (E) are performed, this carbon atom concentration can be determined by measuring the surface of the catalyst layer immediately after the CNTs have been peeled and the steps are performed. Here, "immediately after" means that no other steps are included between the previous step and the measurement of the carbon atom concentration. In the CNT manufacturing method of the present invention, the carbon atom concentration on the surface of the catalyst layer from which the carbon nanotubes have been peeled in the peeling step (B) is less than 50 atomic %, so that high-quality CNTs can be obtained even if carbon nanotubes are formed again on the catalyst layer from which the CNTs have been peeled in the second formation step (C).

[0054] <Cleaning process (D)> In the washing step (D), the catalyst layer (catalyst layer of the used substrate) from which the CNTs have been peeled in the peeling step (B) is washed. Note that the washing treatment of the catalyst layer may be repeated multiple times.

[0055] The method for cleaning the catalyst layer is not particularly limited, and examples thereof include a method of rinsing the catalyst layer of the used substrate with water and wiping it with a cloth, a method of contacting the catalyst layer of the used substrate with an acid such as nitric acid, hydrochloric acid, or hydrofluoric acid, a method of incinerating impurities on the catalyst layer of the used substrate using an oxygen plasma reactor or a UV ozone cleaner, and a method of contacting the catalyst layer of the used substrate with a liquid containing fine bubbles with an average bubble diameter of 50 μm or less.

[0056] Furthermore, after the cleaning step (D), a polishing step may be carried out as a separate step from the cleaning step (D). The polishing step is preferably carried out by impinging a liquid on the used substrate to polish the catalyst layer, and more preferably by impinging a wet blasting slurry, which is made by dispersing an abrasive in a dispersion medium, on the surface of the catalyst layer of the used substrate to physically polish the catalyst layer of the used substrate. Here, the surface of the used substrate that has been subjected to the wet blasting treatment may be washed with water and then wiped with a cloth or dried by blowing air. Furthermore, the catalyst layer may remain on the used substrate after the polishing process, or may be removed by wet blasting. Even if the catalyst layer is removed, there is no adverse effect on the subsequent CNT generation if a catalyst layer is formed again by the catalyst formation process described below.

[0057] Examples of abrasives contained in the wet blasting slurry include alumina, silicon carbide, resin, glass, zirconia, stainless steel, and combinations thereof. Among these, alumina is preferred. The average particle size of the abrasive is preferably 1 μm or more, more preferably 2 μm or more, and preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. If the average particle size is 1 μm or more, impurities such as carbon components remaining on the used substrate can be efficiently removed, and if it is 30 μm or less, the surface of the used substrate will not be excessively roughened after wet blasting. In the present invention, the "average particle size" of the abrasive is the particle size at 50% of the cumulative height (d S -50 value).

[0058] The dispersion medium for the slurry for wet blasting is not particularly limited as long as it can disperse the abrasive, but for example, water can be used. The concentration of the abrasive in the wet blasting slurry is preferably 5% by volume or more, more preferably 7.5% by volume or more, even more preferably 10% by volume or more, and preferably 25% by volume or less, more preferably 22.5% by volume or less, and even more preferably 20% by volume or less. If the concentration of the abrasive in the slurry is 5% by volume or more, impurities such as carbon components remaining on the used substrate can be efficiently removed, and if it is 25% by volume or less, a decrease in processing efficiency due to collisions between the abrasives can be suppressed.

[0059] The wet blasting slurry can then be accelerated by compressed air using, for example, a projectile gun, and then struck against the catalyst layer of the used substrate. The pressure of the compressed air is not particularly limited, but is preferably 0.03 MPa or more, more preferably 0.05 MPa or more, and is preferably 0.3 MPa or less, and more preferably 0.2 MPa or less. If the pressure of the compressed air is within the above range, the slurry containing the abrasive can be uniformly atomized, and the surface of the used substrate can be uniformly treated.

[0060] The distance from the projection nozzle of the projection gun to the surface of the used substrate is preferably 5 mm or more, more preferably 10 mm or more, and even more preferably 15 mm or more, and is preferably 50 mm or less, more preferably 45 mm or less, and even more preferably 40 mm or less. If the distance from the projection nozzle of the projection gun to the surface of the used substrate is within the above-mentioned range, the surface of the used substrate can be treated efficiently and uniformly.

[0061] Furthermore, the projection angle φ of the wet blasting slurry (angle with respect to the surface of the used substrate, 0°≦φ≦90°) is preferably 80° or more, more preferably 85° or more, and even more preferably 90° (i.e., perpendicular to the surface of the used substrate). If the projection angle φ is 80° or more, the surface of the used substrate can be treated efficiently and uniformly.

[0062] The type of projection gun used in the wet blasting treatment is not particularly limited, and examples include nozzle and wide slit projection guns. Although the specific mode of wet blasting using a projection gun is not particularly limited, for example, a preferred mode is to transport the used substrate horizontally and spray the wet blasting slurry onto the transported used substrate from a projection gun fixed above the used substrate. The transport speed of the used substrate is not particularly limited, but is preferably about 10 to 100 mm / sec.

[0063] <Oxidation treatment step (E)> In the oxidation treatment step (E), the catalyst layer (catalyst layer of the used substrate) from which the CNTs have been peeled in the peeling step (B) is subjected to an oxidation treatment. Note that the oxidation treatment of the catalyst layer may be repeated multiple times. The method for oxidizing the catalyst layer is not particularly limited, and examples thereof include a method in which an oxygen source (oxidizing gas) is introduced while heating the catalyst layer of the used substrate, thereby converting carbon present on the surface of the catalyst layer of the used substrate into carbon dioxide.

[0064] <Second forming step (C)> In the second formation step (C), CNTs are formed on the catalyst layer from which the CNTs have been peeled. That is, in the second formation step (C), CNTs are formed on the catalyst layer of a used CNT production substrate on which at least one CNT synthesis has been performed. The method for forming CNTs on the catalyst layer is the same as in the first formation step (A) described above. Here, before forming CNTs on the catalyst layer from which the CNTs have been peeled, a catalyst support layer formation step of newly forming a catalyst support layer on the catalyst layer from which the CNTs have been peeled may be included, or a catalyst layer formation step of newly forming a catalyst layer on the catalyst layer from which the CNTs have been peeled or on the newly formed catalyst support layer may be included.

[0065] [Catalyst support layer formation process] The catalyst support layer may be formed on the catalyst layer from which the CNTs have been peeled using either a wet process or a dry process (such as sputtering deposition). From the viewpoints of the simplicity of the film formation apparatus, high throughput, and low raw material costs, the wet process is preferred.

[0066] Hereinafter, as an example, a case where a catalyst support layer is formed by a wet process will be described. The wet process for forming the catalyst support layer consists of the steps of applying coating solution A, which is made by dissolving a metal organic compound and / or metal salt containing the elements that will become the catalyst support layer in an organic solvent, onto a substrate, and then heating the coating solution. A stabilizer may be added to coating solution A to suppress excessive condensation polymerization reactions of the metal organic compound and metal salt.

[0067] Here, for example, when an alumina membrane is used as the catalyst support layer, aluminum alkoxides such as aluminum trimethoxide, aluminum triethoxide, aluminum tri-n-propoxide, aluminum tri-i-propoxide, aluminum tri-n-butoxide, aluminum tri-sec-butoxide, and aluminum tri-tert-butoxide can be used as the metal organic compound and / or metal salt for forming the alumina membrane. Other examples of metal organic compounds for forming the alumina membrane include complexes such as tris(acetylacetonato)aluminum(III). Examples of metal salts include aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum bromide, aluminum iodide, aluminum lactate, basic aluminum chloride, and basic aluminum nitrate. Among these, aluminum alkoxides are preferred. These can be used alone or in a mixture of two or more.

[0068] The stabilizer is preferably at least one selected from the group consisting of β-diketones and alkanolamines. These compounds may be used alone or in combination of two or more. Examples of β-diketones that can be used include acetylacetone, methyl acetoacetate, ethyl acetoacetate, benzoylacetone, dibenzoylmethane, benzoyltrifluoroacetone, furoylacetone, and trifluoroacetylacetone, with acetylacetone and ethyl acetoacetate being particularly preferred. Examples of alkanolamines that can be used include monoethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylaminoethanol, diisopropanolamine, and triisopropanolamine, with secondary or tertiary alkanolamines being preferred.

[0069] As the organic solvent, various organic solvents such as alcohols, glycols, ketones, ethers, esters, hydrocarbons, etc. can be used, but it is preferable to use alcohols or glycols because they have good solubility for metal organic compounds and metal salts. These organic solvents may be used alone or in combination of two or more. As the alcohol, methanol, ethanol, isopropyl alcohol, etc. are preferred in terms of ease of handling and storage stability.

[0070] The amount of the metal organic compound and / or metal salt in Coating Solution A is not particularly limited, but is preferably 0.1 g or more, more preferably 0.5 g or more, and preferably 30 g or less, more preferably 5 g or less, per 100 mL of organic solvent. The amount of stabilizer in Coating Solution A is not particularly limited, but is preferably 0.01 g or more, more preferably 0.1 g or more, and preferably 20 g or less, more preferably 3 g or less, per 100 mL of organic solvent.

[0071] The coating liquid A may be applied by any method such as spraying, brushing, spin coating, or dip coating, but from the viewpoints of productivity and film thickness control, dip coating is preferred.

[0072] Heating after applying Coating Solution A can be carried out at a temperature ranging from 50°C to 400°C for a period of 5 minutes to 3 hours, depending on the type of catalyst-supported layer. Heating initiates hydrolysis and condensation polymerization reactions of the applied metal organic compound and / or metal salt, and a cured coating (catalyst-supported layer) containing metal hydroxide and / or metal oxide is formed on the surface of the catalyst layer from which the CNTs have been peeled.

[0073] [Catalyst layer formation process] The catalyst layer may be formed by either a wet process or a dry process (such as sputtering deposition), similar to the catalyst support layer. From the viewpoints of the simplicity of the film formation apparatus, the high throughput, and the low cost of raw materials, the wet process is preferred.

[0074] Hereinafter, as an example, a case where a catalyst layer is formed by a wet process will be described. The wet process for forming the catalyst layer consists of the steps of applying coating solution B, which is made by dissolving metal organic compounds and / or metal salts containing the elements that will act as catalysts for CNT synthesis in an organic solvent, onto a substrate, followed by a heating step. Coating solution B may contain a stabilizer to suppress excessive condensation polymerization reactions of the metal organic compounds and metal salts.

[0075] Here, for example, when iron is used as a catalyst for CNT synthesis, the metal organic compound and / or metal salt used to form the iron thin film that serves as the catalyst layer can be iron pentacarbonyl, ferrocene, iron acetylacetonate (II), iron acetylacetonate (III), iron trifluoroacetylacetonate (II), iron trifluoroacetylacetonate (III), etc. Examples of metal salts include inorganic iron salts such as iron sulfate, iron nitrate, iron phosphate, iron chloride, and iron bromide, and organic iron salts such as iron acetate, iron oxalate, iron citrate, and iron lactate. Among these, organic iron salts are preferred. These can be used alone or as a mixture of two or more.

[0076] The stabilizer and organic solvent for Coating Solution B may be the same as those for Coating Solution A. The contents thereof may also be the same as those for Coating Solution A.

[0077] Furthermore, the coating method for Coating Liquid B can be the same as that for Coating Liquid A. Furthermore, heating after coating Coating Liquid B can be performed in the same manner as for Coating Liquid A.

[0078] This catalyst layer forming step produces a used substrate having a catalyst layer newly formed on its surface.

[0079] The total thickness of the newly formed catalyst support layer and the catalyst layer is preferably 5.0 nm or more, more preferably 10 nm or more. The total thickness of the catalyst support layer and catalyst layer formed on the substrate (when a used substrate is reused to form a new catalyst support layer and catalyst layer on the used catalyst layer, the total thickness of the used catalyst support layer and catalyst layer and the total thickness of the newly formed catalyst support layer and catalyst layer) is preferably more than 10 nm, more preferably 15 nm or more. The total thickness of the catalyst support layer and catalyst layer can be 3 μm or less.

[0080] <Carbon atom concentration> In the first formation step (A), the carbon atom concentration on the surface of the catalyst layer before forming CNTs is preferably less than 50 atomic %, more preferably 40 atomic % or less, and particularly preferably 25 atomic % or less. When the carbon atom concentration is within the preferred range, the quality and yield of the obtained CNTs can be further improved.

[0081] After the first formation step (A), in the peeling step (B), the carbon atom concentration on the surface of the catalyst layer from which the CNTs have been peeled needs to be less than 50 atomic %, preferably 48 atomic % or less, and more preferably 45 atomic % or less. When the carbon atom concentration is within the preferred range, the quality and yield of the obtained CNTs can be further improved.

[0082] In addition, when the "carbon atom concentration on the surface of the catalyst layer of the CNT generation substrate before use that has never undergone CNT formation" is defined as "A0" (for example, "A0" in Example 1 described later), and the "carbon atom concentration on the surface of the catalyst layer of the used CNT generation substrate after the CNTs formed in the nth time have been peeled" is defined as "An" (for example, "A1 to A3" in Example 1 described later), the ratio of the carbon atom concentration (An / A0) is preferably less than 2. If the ratio of the carbon atom concentration (An / A0) is within the above range, the quality and yield of the obtained carbon nanotubes can be kept good.

[0083] The "carbon atom concentration A0 on the surface of the catalyst layer of the CNT generation substrate before use that has never undergone CNT formation" (the carbon atom concentration A0 on the surface of the catalyst layer before CNT formation) is preferably less than 50 atomic %, more preferably 40 atomic % or less, and particularly preferably 25 atomic % or less. If the "carbon atom concentration A0 on the surface of the catalyst layer of the CNT generation substrate before use that has never undergone CNT formation" is within the above range, the quality and yield of the obtained CNTs can be further improved.

[0084] <Continuous production of CNTs> When manufacturing CNTs while reusing the used substrate, the formation and peeling of CNTs are repeatedly carried out. Thus, if the used substrate is reused for the formation of CNTs, the manufacturing cost of CNTs can be further reduced.

[0085] Here, when the formation and peeling of CNTs are repeatedly carried out, considering performing a cleaning process (D) etc. in the peeling step (B), the carbon atom concentration on the surface of the portion where the catalyst layer is newly formed when forming CNTs for the Xth time (where X is an integer of 2 or more) is generally approximately equal to the carbon atom concentration on the surface of the catalyst layer after performing the formation and peeling of CNTs for the (X - 1)th time. For example, the carbon atom concentration on the surface of the portion where the catalyst layer is newly formed when forming CNTs for the second time is generally approximately equal to the carbon atom concentration on the surface of the catalyst layer after performing the formation and peeling of CNTs for the first time.

[0086] And the number of times of repeatedly carrying out the formation and peeling of CNTs, that is, the number of times of reusing the substrate for CNT generation, is preferably 50 times or more, and more is better from the viewpoint of cost reduction. Although there is no particular limitation, it is usually 100 times or less. If the number of times of reusing the substrate for CNT generation is 100 times or less, deformation of the substrate for CNT generation can be suppressed and the transportability (handling property) of the substrate for CNT generation can be improved.

[0087] <Yield of CNT> [[ID=Yield of CNT]] The yield of CNTs is preferably 1.0 mg / cm 2 or more, more preferably 1.2 mg / cm 2 or more, and particularly preferably 1.5 mg / cm 2 or more.

Examples

[0088] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, the BET specific surface area and the carbon atom concentration of CNTs were evaluated using the following methods, respectively.

[0089] <BET specific surface area> The measurement was carried out using a BET specific surface area measurement device (manufactured by Mount Tech Co., Ltd., HM model-1210). <Carbon atom concentration> The measurement of the carbon atom concentration was performed using X-ray photoelectron spectroscopy (XPS) (manufactured by Ulvac-PHI, PHI-5000 VersaProbeII) that can obtain detailed information on elements existing in the vicinity of the surface within several nanometers. The X-ray was monochromatic Al-Kα, the beam diameter was 100 μm, and the beam output was 25 W - 15 kV. Three 1 cm × 1 cm samples were cut out from the substrate (50 cm × 50 cm: thickness 0.6 mm) used for CNT synthesis as measurement samples, and wide and narrow spectra were obtained at two different points for each sample. The target limits were C, O, N, Al, and Fe existing in the vicinity of the surface. For the obtained spectra, charge correction calibration, background processing, and peak smoothing processing were performed, and the relative carbon atom concentration of the target elements was calculated by semi-quantitative method through integral value comparison considering the relative sensitivity coefficient, and the average value of the six measurements was taken as the carbon atom concentration (atomic %) on the substrate surface.

[0090] (Example 1) <First synthesis of CNT> [Preparation of unused CNT production substrate] 1.9 g of aluminum tri-sec-butoxide, which is an aluminum compound, was dissolved in 100 mL of 2-propanol, which is an organic solvent. Further, 0.9 g of triisopropanolamine, which is a stabilizer, was added and dissolved to prepare coating solution A. Also, 174 mg of iron acetate, which is an iron compound, was dissolved in 100 mL of 2-propanol, which is an organic solvent. Further, 190 mg of triisopropanolamine, which is a stabilizer, was added and dissolved to prepare coating solution B. An Fe-Cr alloy SUS430 substrate (manufactured by JFE Steel Corporation, 50 cm × 50 cm, thickness 0.3 mm, Cr 18%) as a substrate was prepared. ​​The surface of the prepared substrate was then coated with the above-mentioned Coating Solution A by dip coating at a room temperature of 25°C and a relative humidity of 50%. Specifically, the substrate was immersed in Coating Solution A, held there for 20 seconds, and then pulled up at a speed of 10 mm / sec. The substrate was then air-dried for 5 minutes, heated in an air environment at 300°C for 30 minutes, and cooled to room temperature to form a 14 nm-thick alumina thin film on the substrate as a catalyst support layer, which was an underlayer. Next, in an environment of room temperature 25°C and relative humidity 50%, the above-mentioned coating liquid B was applied by dip coating onto the alumina thin film provided on the substrate. Specifically, the substrate with the alumina thin film on it was immersed in coating liquid B, held for 20 seconds, and then pulled up at a pulling speed of 3 mm / sec. Thereafter, the substrate was air-dried for 5 minutes (drying temperature 45°C) to form a 1 nm-thick iron thin film as a catalyst layer on the substrate, and an unused CNT generating base material was obtained. The carbon atom concentration (A0) of the surface of the catalyst layer formed on the surface of the unused CNT growth substrate (substrate before CNT formation) was measured and found to be 23.44 (atomic %). [CNT formation] Next, the prepared unused CNT growth substrate was placed in a furnace at a temperature of 750°C and a pressure of 1.02 × 10 5 The device was placed in the reaction chamber of a CVD device maintained at 100 Pa, and 100 sccm of He and 900 sccm of H2 were introduced into the reaction chamber for 6 minutes. This reduced the CNT synthesis catalyst (iron) and promoted its microparticulation, creating a state suitable for CNT growth (a state in which numerous nanometer-sized catalyst microparticles were formed) (formation process). The density of the catalyst microparticles at this time was 1 x 10 12 ~1×10 14 pieces / cm 2 After that, the furnace temperature was adjusted to 750°C and the furnace pressure to 1.02 × 10 5He: 800 sccm, C2H4: 100 sccm, H2: 100 sccm, and HO: HO concentration of 200 ppm were supplied for 10 minutes into the reaction chamber maintained at 200 Pa. As a result, single-walled CNTs grew from each catalyst particle on the surface of the CNT growth substrate (CNT growth process). After the CNT growth process was completed, only 1000 sccm of He was supplied into the reaction chamber, and the remaining mixed gas (raw material gas + hydrogen gas) and catalyst activation material were removed. As a result, aligned CNT aggregates were formed on the surface of the catalyst layer formed on the surface of the CNT generation substrate (CNT formation process). [Recovery of CNTs] The aligned CNT aggregates grown on the catalyst layer were then peeled off from the surface of the CNT production substrate. Specifically, a plastic spatula with a sharp tip was used to peel off the aligned CNT aggregates. During peeling, the sharp tip of the spatula was placed on the boundary between the aligned CNT aggregates and the substrate, and the sharp tip was moved along the surface of the CNT production substrate so as to scrape off the aligned CNT aggregates from the CNT production substrate. In this way, the aligned CNT aggregates were peeled off from the CNT production substrate, and a used substrate was obtained (peeling step (B)). The yield and specific surface area of ​​the obtained CNTs were measured. As shown in Table 1, the yield was 1.48 (mg / cm 2 ) and the specific surface area is 1502(m 2 / g). [Cleaning of used substrates] The obtained used substrate was washed with water (washing step (D)), and the carbon atom concentration (A1) on the surface of the used substrate after washing with water was measured. As shown in Table 1, the carbon atom concentration (A1) was 41.44 (atomic %), which was below 50 (atomic %). Thereafter, the obtained used substrate was subjected to polishing treatment by wet blasting using a wet blasting device (PFE300, manufactured by Maco Corporation) equipped with a wide slit type projection gun (polishing treatment step). The wet blasting slurry used in the wet blasting process was prepared by dispersing alumina abrasives (abrasive grains) with an average particle size of 7 μm (corresponding to particle size #2000 specified in JIS R6001 (1998, Fine Powder for Precision Polishing / Electrical Resistance Test Method)) in water as a dispersion medium. The abrasive concentration was 15% by volume. The wet blasting process was carried out once under the following conditions on a used substrate that was transported horizontally below a blast gun at 50 mm / sec. Compressed air pressure of the projection gun: 0.09 MPa Distance from the projection nozzle of the projection gun to the surface of the used substrate: 30 mm Projection angle φ:90°

[0091] <Second CNT synthesis> [Formation of catalyst layer] On top of the catalyst layer (catalyst layer formed in the first CNT synthesis) formed on the surface of the cleaned used substrate, a catalyst support layer (alumina thin film) with a thickness of 14 nm was formed (catalyst support layer formation step), and a catalyst layer (iron thin film) with a thickness of 1 nm was formed (catalyst layer formation step) in the same manner as in the first CNT synthesis (number of times the used substrate was reused: 1). As a result, the total thickness of the catalyst support layer and catalyst layer was 30 nm. [CNT formation] In the same manner as in the first synthesis of CNTs, CNTs were formed on a catalyst layer (thin iron film) formed on the surface of the cleaned used substrate (CNT formation step). [Recovery of CNTs] In the same manner as in the first synthesis of CNTs, the aligned CNT aggregates were peeled off from the surface of the cleaned used substrate on which the CNTs had been formed, to obtain a used substrate (peeling step (B)). The yield and specific surface area of ​​the obtained CNTs were then measured. As shown in Table 1, the yield was 1.73 (mg / cm 2 ) and the specific surface area is 1351 (m 2 / g). [Cleaning of used substrates] The used substrate was washed in the same manner as in the first CNT synthesis (washing step (D)). The carbon atom concentration (A2) of the catalyst layer formed on the surface of the used substrate after the cleaning step (D) (after water washing and before wet blasting) was measured. As shown in Table 1, the carbon atom concentration (A2) was 35.89 (atomic %). <Third CNT synthesis> [Formation of catalyst layer] On the catalyst layer formed on the surface of the cleaned used substrate (catalyst layer formed in the second CNT synthesis), a catalyst support layer (alumina thin film) with a thickness of 14 nm was formed (catalyst support layer formation step), and a catalyst layer (iron thin film) with a thickness of 1 nm was formed (catalyst layer formation step) in the same manner as in the first CNT synthesis (used substrate reused twice). As a result, the total thickness of the catalyst support layer and catalyst layer was 45 nm. [CNT formation] In the same manner as in the first synthesis of CNTs, CNTs were formed on a catalyst layer (thin iron film) formed on the surface of the cleaned used substrate (CNT formation step). [Recovery of CNTs] In the same manner as in the first synthesis of CNTs, the aligned CNT aggregates were peeled off from the surface of the cleaned used substrate on which the CNTs had been formed, to obtain a used substrate (peeling step (B)). The yield and specific surface area of ​​the obtained CNTs were then measured. As shown in Table 1, the yield was 1.76 (mg / cm 2 ) and the specific surface area is 1364(m 2 / g). [Cleaning of used substrates] The used substrate was washed in the same manner as in the first CNT synthesis (washing step (D)). Then, the carbon atom concentration (A3) of the catalyst layer formed on the surface of the used substrate after the cleaning step (D) (after water washing and before wet blasting) was measured. As shown in Table 1, the carbon atom concentration (A3) was 43.32 (atomic %).

[0092] Example 2 <First CNT synthesis> The same procedures as in the first CNT synthesis in Example 1 were carried out, except that instead of using a mixed gas containing hydrogen in the formation of CNTs, only the raw material gas was used (no hydrogen was used). The catalyst support layer, catalyst layer, and CNT formation, CNT recovery, cleaning of the used substrate, CNT yield and specific surface area, and measurement of the carbon atom concentration (A0) on the surface of the catalyst layer formed on the surface of an unused CNT production substrate (substrate before CNT formation) were carried out. The carbon atom concentration (A0) was 25.61 (atomic %). Furthermore, as shown in Table 2, the CNT yield was 1.96 (mg / cm 2 ) and the specific surface area is 1310(m 2 / g). [Oxidation treatment of cleaned substrate] Next, the cleaned substrate was placed in a thermostatic chamber for 1 hour under the conditions of oxidizing gas: N2 containing 1% O2, and chamber temperature: 400°C, and oxidation treatment was performed (oxidation treatment step (E)). The carbon atom concentration (A1) on the surface of the oxidized substrate was measured. As shown in Table 2, the carbon atom concentration (A1) was 40.87 (atomic %). <Second CNT synthesis> The formation of the catalyst support layer, catalyst layer, and CNTs, the recovery of CNTs, the cleaning of the used substrate, and the measurement of the CNT yield and specific surface area were carried out in the same manner as in the second CNT synthesis of Example 1, except that instead of using a mixed gas containing hydrogen in the formation of CNTs, only the raw material gas was used (hydrogen was not used). As shown in Table 2, the CNT yield was 1.91 (mg / cm 2 ) and the specific surface area is 1285(m 2 / g). [Oxidation treatment of cleaned substrate] As in the first CNT synthesis, the cleaned substrate was oxidized and the carbon atom concentration (A2) on the surface of the oxidized substrate was measured. As shown in Table 2, the carbon atom concentration (A2) was 46.32 (atomic %). <Third CNT synthesis> The formation of the catalyst support layer, catalyst layer, and CNTs, the recovery of CNTs, the cleaning of the used substrate, and the measurement of the CNT yield and specific surface area were carried out in the same manner as in the third CNT synthesis in Example 1, except that instead of using a mixed gas containing hydrogen in the formation of CNTs, only the raw material gas was used (hydrogen was not used). As shown in Table 2, the CNT yield was 1.88 (mg / cm 2 ) and the specific surface area is 1244(m 2 / g). [Oxidation treatment of cleaned substrate] As in the first CNT synthesis, the cleaned substrate was oxidized and the carbon atom concentration (A3) on the surface of the oxidized substrate was measured. As shown in Table 2, the carbon atom concentration (A3) was 46.79 (atomic %).

[0093] (Comparative Example 1) <First CNT synthesis> The same procedures as in the first CNT synthesis in Example 1 were carried out, except that instead of using a mixed gas containing hydrogen in the CNT formation, only the raw material gas was used (no hydrogen was used). The formation of the catalyst support layer, catalyst layer, and CNTs, the recovery of CNTs, the cleaning of the used substrate, the measurement of CNT yield and specific surface area, and the carbon atom concentration (A0) of the catalyst layer surface formed on the surface of an unused CNT production substrate (substrate before CNT formation) and the carbon atom concentration (A1) of the surface of the used substrate after the cleaning step (D) (after water washing and before wet blasting) were measured. The carbon atom concentration (A0) was 23.44 (atomic %). As shown in Table 3, the CNT yield was 1.65 (mg / cm). 2 ) and the specific surface area is 1411(m 2 / g). <Second CNT synthesis> The formation of the catalyst support layer, catalyst layer, and CNTs, the recovery of CNTs, the cleaning of the used substrate, and the measurement of the CNT yield and specific surface area were carried out in the same manner as in the second CNT synthesis of Example 1, except that instead of using a mixed gas containing hydrogen in the formation of CNTs, only the raw material gas was used (hydrogen was not used). As shown in Table 3, the CNT yield was 0.53 (mg / cm 2 ) and the specific surface area is 635(m2 / g).

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097] As shown in Tables 1 and 2, in Examples 1 and 2, in the CNT formation in the second and third CNT synthesis, the carbon atom concentrations (A1 and A2) of the used catalyst layer surface on the surface of the used substrate after the peeling step (B) were both less than 50 atomic %. 2 / g or more, CNTs with a specific surface area of ​​1.0 g / cm 2 The above yield was obtained.

[0098] On the other hand, as shown in Table 3, in Comparative Example 1, in the CNT formation in the second CNT synthesis, the carbon atom concentration (A1) of the used catalyst layer surface on the surface of the used substrate after the peeling step (B) was 50 atomic % or more, and the specific surface area of ​​the obtained CNTs was 800 m 2 / g, and the CNT yield was 1.0 g / cm 2 It was less than.

[0099] The results in Tables 1, 2, and 3 show that high-quality CNTs can be produced efficiently if the carbon atom concentration on the surface of the used catalyst layer from which the CNTs have been peeled after CNT formation is less than 50 atomic %. [Industrial Applicability]

[0100] According to the method for producing CNTs of the present invention, high-quality CNTs can be produced efficiently.

Claims

1. A method for producing carbon nanotubes, comprising the steps of: producing carbon nanotubes using a substrate for producing carbon nanotubes, the substrate comprising a substrate and a catalyst layer provided on the substrate; A first forming step (A) of forming carbon nanotubes on the catalyst layer; a peeling step (B) of peeling off the carbon nanotubes formed on the catalyst layer and cleaning the catalyst layer from which the carbon nanotubes have been peeled off; a polishing step of polishing the catalyst layer after the cleaning; a second forming step (C) of forming carbon nanotubes again on the catalyst layer from which the carbon nanotubes have been peeled off after the polishing step; the carbon atom concentration on the surface of the catalyst layer cleaned in the peeling step (B) is less than 50 atomic %; The second formation step (C) includes a catalyst support layer formation step of newly forming a catalyst support layer on the surface of the catalyst layer before forming carbon nanotubes, and a catalyst layer formation step of newly forming a catalyst layer on the newly formed catalyst support layer, thereby forming carbon nanotubes on the newly formed catalyst layer.

2. 2. The method for producing carbon nanotubes according to claim 1, wherein in at least one of the first forming step (A) and the second forming step (C), the carbon nanotubes are formed using a mixed gas containing a carbon nanotube raw material gas and hydrogen.

Citation Information

Patent Citations

  • Method of manufacturing monolayer carbon nanotube

    JP2006027948A

  • Method for production of carbon fiber, substrate cartridge, and thermal CVD device

    JP2007091485A

  • Reused substrate for producing carbon nanotube, substrate for producing carbon nanotube, and method for manufacturing the substrate

    JP2011068501A

  • Production method of fibrous carbon NANO structure

    JP2017165617A

  • Method for production of carbon nanotube

    WO2008029927A1